KORELASI ANTARA PENGETAHUAN LINGKUNGAN DENGAN SIKAP TERHADAP LINGKUNGAN PADA MASYARAKAT BANJAR BIAUNG DESA KESIMAN KERTALANGU DENPASAR - Ni Nyoman Parmithi; I Gede Putra Wirawa N (Emasains : Jurnal Edukasi Matematika dan Sains, 2016)
This study aims to determine the correlation between the knowledge society with its attitude towards the environment in the village of Banjar Biaung Kesiman Kertalangu Denpasar, the 2014.Populasi in this study were residents in the village of Banjar Biaung Kesiman Kertalangu Denpasar the number of residents in 1010 and used as a sample of 50 members community using Proportional Stratified Random Sampling. Data collection was conducted by questionnaire and the data obtained were then analyzed by simple correlation analysis. Results of regression analysis regression line equation y = 10.19 + 0.88 X. From the above regression equation can be interpreted that if the value of the knowledge society incremented by 1, then the average value of its attitude to the environment increased to 0.88, or any value knowledge society increases of 50, then the value of his attitude to the environment at 44. From the analysis of the data obtained r value of 0.789. This is in relation to the interpretation of the correlation coefficient indicates a strong relationship. The correlation coefficient indicates that the variance between the variables that occur in the knowledge society with its attitude towards the environment by 62.3% and the remaining 37.7% is determined by other factors. Thus concluded that there is a significant relationship between the knowledge society with its attitude towards the environment in the village of Banjar Biaung Kesiman Kertalangu Denpasar, 2014.